Using national virtual maternal death reviews to improve the quality of care during Pregnancy, labour and birth, and Postpartum in Tanzania - Ahmad Mohamed Makuwani; Sunday Alfred Dominico; Secilia Kapalata Ngweshemi; Golden Mwakibo Masika; Rose Mpembeni; Charles Ameh; Mzee Masumbuko Nassoro; Phineas Sospeter; Habib Ismail; Tumaini Nagu; Matilda Ngarina; Edwin Lugazia; et al. (PLoS ONE, 2026)
Background Tanzania has implemented the Maternal and Perinatal Death Surveillance and Response (MPDSR) system for more than a decade. However, multiple assessments have shown that the quality of maternal death reviews at facility and district levels has often been limited by inadequate specialist participation, weak root-cause analysis, and insufficient follow-through on action plans. These limitations have reduced the effectiveness of MPDSR in driving quality improvement and preventing avoidable maternal deaths. To address these gaps and strengthen accountability and clinical learning, the Ministry of Health introduced daily Virtual Maternal Death Reviews (VMDR) in 2021. This study describes the implementation and outcomes of VMDR from 2022 to 2023. Methods A descriptive observational study was conducted using a mixed-methods approach. The analysis included maternal deaths that were notified through the national MPDSR system and subsequently selected for VMDR sessions between January 2022 and December 2023. Cases were eligible if they met the WHO definition of a maternal death and had sufficient clinical documentation from facility or district review committees to allow determination of the cause of death and contributing factors. Quantitative data were summarised using descriptive statistics, while qualitative insights from VMDR discussions were synthesised to identify modifiable clinical and system-level factors and response actions. Results A total of 369 VMDR sessions were conducted, reviewing 687 maternal deaths across all regions. The leading causes of death were obstetric haemorrhage (49%), hypertensive disorders of pregnancy (16%), and anaesthesia-related complications (10%). Common modifiable contributing factors included inadequate clinical competency (82%), suboptimal provider practices and attitudes (69%), weak leadership and accountability (42%), and gaps in surgical and anaesthesia care. VMDR participation facilitated improved oversight and prompted remedial actions such as redeployment of specialists, improvement of essential supplies, and initiation of structured mentorship and continuing medical education. Conclusion The VMDR model strengthened the quality and consistency of maternal death reviews and improved accountability in responding to identified gaps. Sustaining VMDR requires continued leadership to maintain confidentiality in line with existing culture and norms.